2012
DOI: 10.1155/2012/510458
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index, Waist Circumference, Body Fat, Fasting Blood Glucose in a Sample of Moroccan Adolescents Aged 11–17 Years

Abstract: Objectives. The study aimed to assess the relationship between body fat and each of body mass index (BMI) and waist circumference (WC), and to test the effectiveness of fat mass (FM), percent of body fat (PBF), BMI, and WC in predicting high levels of fasting blood glucose (FBG). Methods. A total of 167 adolescents aged 11–17 years were recruited from Rabat region. BMI and WC were determined using standard equipments. FM and PBF were derived from isotope dilution technique. FBG was determined by the hexokinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
20
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 52 publications
10
20
2
1
Order By: Relevance
“…The strong positive correlations observed between BMI and percent body fat was similar to the results from previous studies [26,[29][30][31]. In a cohort of Swiss school children aged 8-11 years, BMI and body fat were highly correlated particularly in the upper half of the BMI regardless of gender, suggesting that BMI is a good proxy for body fat in children with higher BMI.…”
Section: Discussionsupporting
confidence: 88%
“…The strong positive correlations observed between BMI and percent body fat was similar to the results from previous studies [26,[29][30][31]. In a cohort of Swiss school children aged 8-11 years, BMI and body fat were highly correlated particularly in the upper half of the BMI regardless of gender, suggesting that BMI is a good proxy for body fat in children with higher BMI.…”
Section: Discussionsupporting
confidence: 88%
“…A similar tendency was also observed in a previous adult study [9]; however, few studies have reported on this correlation in adolescents. Mehdad et al [28] showed that fasting blood glucose levels are highly correlated with fat mass and PBF in overweight-obese female adolescents aged 11-17 years, a population similar in age to our study sample. Cruz et al [29] reported that this positive relationship in the overweight-obese group of girls may be explained by the clustering of metabolic syndrome factors, which are risk factors for type 2 diabetes.…”
Section: Discussionsupporting
confidence: 68%
“…Previous mouse studies suggested the serum glucose levels were decreased through caloric restriction 34, 35 . Further, serum glucose levels are positively correlated with body mass index (BMI) observed in human studies 36, 37 . Tempol serum metabolite profiles identified decreased glucose and amino acids levels consistent with the decreased hepatic glucose and amino acid reserves, improved insulin sensitivity, and lean phenotype.…”
Section: Discussionmentioning
confidence: 93%